Analisis Tindak Kejahatan: Bukti Empiris dari IFLS 2007 - , Siti Rusdiyanti, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nation security is most important factor for economic activities, because crime has a negative impact for community. Thus, every nation has a relation for controlling crimes. Awakening a sense of security of citizens is reflected in their behavior related to the way they protect themselves from the property and the potential risk of crime against them. The fear of crime refers to the fear of being a victim of crime as opposed to the actual probability of being a victim of crime. Fear of crime associated with crime rates. When the crime rate is high, then the fear of crime will be high anyway. Preventing efforts against crime is part of the criminal policy of using the criminal law. Controlling crimes can be done by paying attention on crime report in each area. According that, crime reporting decision is important thing. Victims reporting crime decision has relations with type of crime, victim education background, socio-economic charactheristics and area where crime happened. The research aims to analyze the influence of victim backgrounds dan crime types to crime reporting decision. The research uses empirical evidence from Indonesia Family Life Survey (IFLS) wave 4, 2007. Logistic regression model is used to estimate whiches victim characteristic, crime area, and crime types influence victims to make decision. Victim crime decision at household level is influenced by crime types and socio-economic characteristic of household. The research uses logistic regression model to test the influence of each independent variable (level of education, area, income, asset belonging, types of crime) to variable dependent crime reporting decision. Victim has reasons (motivations) to report or not report crime, but IFLS only asked victims motivation for not reporting. The level of observasion is different so this variable excluded from the model. The result shows that type of crime has a significant effect to crime reporting decision. The research also counts crime multiplier. Crime multiplier is used to estimate level of crime in Indonesia